2015
DOI: 10.1016/j.schres.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heschl's gyrus and planum temporale in patients with schizophrenia and bipolar disorder: A proton magnetic resonance spectroscopy study

Abstract: Background Superior temporal cortices include brain regions dedicated to auditory processing and several lines of evidence suggest structural and functional abnormalities in both schizophrenia and bipolar disorder within this brain region. However, possible glutamatergic dysfunction within this region has not been investigated in adult patients. Methods Thirty patients with schizophrenia (38.67 ± 12.46 years of age), 28 euthymic patients with bipolar I disorder (35.32 ± 9.12 years of age), and 30 age-, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 83 publications
(117 reference statements)
1
34
2
1
Order By: Relevance
“…For example, Glu concentrations in the left Heschl’s Gyrus and Planum Temporale of the superior temporal gyrus of patients with schizophrenia and BDd have been proved to be lower than healthy cohorts10. Comparing to schizophrenia patients and healthy cohorts, lower Glu, NAA, Cr and Inositol in patients with BDd suggested that a possible location-specific abnormality was existed in the dominant hemisphere of auditory cortices in patients with BDd11. As the main excitatory transmitter in the human brain, altered Glx was found in gray matter areas of patients with BDd1213.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Glu concentrations in the left Heschl’s Gyrus and Planum Temporale of the superior temporal gyrus of patients with schizophrenia and BDd have been proved to be lower than healthy cohorts10. Comparing to schizophrenia patients and healthy cohorts, lower Glu, NAA, Cr and Inositol in patients with BDd suggested that a possible location-specific abnormality was existed in the dominant hemisphere of auditory cortices in patients with BDd11. As the main excitatory transmitter in the human brain, altered Glx was found in gray matter areas of patients with BDd1213.…”
mentioning
confidence: 99%
“…As a putative marker of glial cells, the level of mI has been shown to be significantly reduced in UDd while increased in BDd paitents714. Cr plays a key role in maintaining energy stores, and its level is considered relatively constant141618, but recent research have report that Cr levels are not stable in some psychiatric populations1119.…”
mentioning
confidence: 99%
“…Since auditory hallucinations are one of the most frequent symptoms of schizophrenia and abnormalities of the auditory cortices are associated with hallucinations [15], auditory cortices are among the most relevant brain regions in schizophrenia. In a recent 1 H-MRS study, we have detected metabolic abnormalities within the left hemisphere superior temporal lobe in both schizophrenia and bipolar disorder [16]. Neural synchronization deficits with auditory tasks may indicate GABAergic abnormalities in auditory cortices in bipolar disorder and schizophrenia [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is located in the posterior part of the area on the superior surface of the temporal lobe or, the planum temporale. Heschl's gyrus is also known as transverse temporal gyrus (2,3). The morphology of this gyrus has been reported to be variable (3).…”
Section: Introductionmentioning
confidence: 99%
“…Besides auditory disorders, Heschl's gyrus morphology may be affected in different diseases. For example, it has been reported that the volume of Heschl's gyrus is reduced in patients with schizophrenia (2). Therefore, identification of Heschl's gyrus on sectional imaging techniques, especially on MR imaging is important.…”
Section: Introductionmentioning
confidence: 99%